APLIKASI QUALITY TOOLS UNTUK MENURUNKAN NON CONFORMING PRODUCT PADA INDUSTRI DRY SLS DI INDONESIA: STUDI KASUS PT KCI - Hadiman Nurdin; Lien Herliani Kusumah (Universitas Mercu Buana, 2018)
The purpose of this research is to improve the product quality problem experienced by one of dry SLS manufacturing company in Indonesia. The high number of non conforming product during the past year makes the sales target to be unachievable and caused the loss due to many rework process. Tools are used in this research is to apply the seven tools approach. Flowchart, Pareto chart, and histogram are used to calculate and determine the problem to be fixed. Collection of improvement idea is done by brainstorming and improvement analysis is done by using Fishbone diagram. The results of the improvements made good results are marked by decreasing the number and percentage of non conforming product more than 50 percent of the amount of non conforming product on the previous condition prior to the improvement.